The Influence of Talent Management and Human Resource Management Practices on ASN Performance Through Intervening Variables of Organizational Commitment - Ningrum, Risya Lestari; Lusiana, Desi; Pratminingsih, Sri Astuti (Atestasi : Jurnal Ilmiah Akuntansi, 2023)
This study aims to determine the influence of talent management and human resource management practices on the performance of ASN (State Civil Apparatus) through intervening variables of organizational commitment. This research was conducted at an ASN who worked in the Administrative Bureau of the Head of the Regional Secretariat of West Java Province. The population in this study was 123 ASN people. Meanwhile, the determination of the sample uses the total sampling technique. The research method used through a quantitative approach by taking data using a research instrument in the form of a questionnaire which is then measured on a likert scale. The results of data processing are studied and analyzed using a path analysis model. The findings in this study show that talent management has no significant influence on ASN performance either directly or indirectly through intervening variables. Meanwhile, the variables of human resource management practices have a significant influence on the performance of ASN both directly and indirectly through variable intervening, namely organizational commitment. In this case, other more in-depth research is needed to find out other factors that can affect the performance of ASNs working in the local government environment.